Proses Pembuatan Sarung Goyor di Kabupaten Pemalang - Marselina Nugraheni Fitrisari; M. Suryadi (Jurnal Kajian Bahasa, Sastra dan Pengajaran (KIBASP), 2020)
The purpose of this study is to explain the process of making goyor gloves and reflect cultural phenomena that exist in the village of Wanarejan Pemalang Regency. The method used in this research is descriptive qualitative. The stages in this study began with data collection which was carried out by observation, interview, and note taking techniques. This research data in the form of speech based on the results of interviews with crafters goyor gloves. The next stage is the stage of data analysis carried out by the matching method. The results of the study, the process of making a goyor glove has four main stages. At each major stage there are several steps that have their own names. The name is derived from the culture in the village of Wanarejan. Then the reflection of cultural phenomena in the village of Wanarejan is a form of handicraft which is a picture of the life of the Wanarejan village community, Pemalang Regency. Conclusion, in the process of making the goyor glove there is a reflection of the cultural symptoms of the Wanarejan village community in Pemalang Regency, which existed from ancient times to the present. Keywords: Goyor Sarong, Ethnolinguistics, Wanarejan.